When can an Independent Central Bank offer lower Inflation at no Cost? A Political Economy Analysis - Andrew Hughes Hallett; Maria Demertzis (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
An Independent Central Bank is often associated with being able to achieve low inflation and greater output stability than government run policies. In this paper we examine whether, and under what circumstances, an independent Central Bank can achieve both these targets with only one policy instrument at its disposal. This turns out to be possible in some special cases, or sometimes for limited periods of time, but not in general. It is an outcome which arises when increasingly conservative policies reduce the 2 target, 1 instrument conflicts, rather than from the suppression of any political cycle.
Keywords: 330